Best Answer

If that's 4t3, that indicates that t has been cubed, which is to say it represents t x t x t.

Q: What does the 3 represent in 4t 3?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

r + 2t = -3 . . . . (A)3r - 4t = -9 . . . . (B)2*(A) + (B): 2r + 4t + 3r - 4t = -6 - 95r = - 15 so r = -3substituting in (A), t = 0So the answer is (r, t) = (-3, 0)r + 2t = -3 . . . . (A)3r - 4t = -9 . . . . (B)2*(A) + (B): 2r + 4t + 3r - 4t = -6 - 95r = - 15 so r = -3substituting in (A), t = 0So the answer is (r, t) = (-3, 0)r + 2t = -3 . . . . (A)3r - 4t = -9 . . . . (B)2*(A) + (B): 2r + 4t + 3r - 4t = -6 - 95r = - 15 so r = -3substituting in (A), t = 0So the answer is (r, t) = (-3, 0)r + 2t = -3 . . . . (A)3r - 4t = -9 . . . . (B)2*(A) + (B): 2r + 4t + 3r - 4t = -6 - 95r = - 15 so r = -3substituting in (A), t = 0So the answer is (r, t) = (-3, 0)

t in this problem equals -3. 4t- 8+ 25= 5 -25 -25 4t- 8= -20 +8 +8 4t= -12 /4 /4 t= -3

9t = 4t + 120 9t-4t = 4t - 4t + 120 5t = 120 5t/5 = 120/5 t = 24 24 is your answer

4t + 13t + 2 = 17t + 2

If 4t + 5 = 37, then t = 8.

Related questions

4t-3 is not equal to 13+4t

4t - 3 = 19 4t = 19 +3 = 22 t = 22/4 t = 5.5

r + 2t = -3 . . . . (A)3r - 4t = -9 . . . . (B)2*(A) + (B): 2r + 4t + 3r - 4t = -6 - 95r = - 15 so r = -3substituting in (A), t = 0So the answer is (r, t) = (-3, 0)r + 2t = -3 . . . . (A)3r - 4t = -9 . . . . (B)2*(A) + (B): 2r + 4t + 3r - 4t = -6 - 95r = - 15 so r = -3substituting in (A), t = 0So the answer is (r, t) = (-3, 0)r + 2t = -3 . . . . (A)3r - 4t = -9 . . . . (B)2*(A) + (B): 2r + 4t + 3r - 4t = -6 - 95r = - 15 so r = -3substituting in (A), t = 0So the answer is (r, t) = (-3, 0)r + 2t = -3 . . . . (A)3r - 4t = -9 . . . . (B)2*(A) + (B): 2r + 4t + 3r - 4t = -6 - 95r = - 15 so r = -3substituting in (A), t = 0So the answer is (r, t) = (-3, 0)

T+(3-2t)=4t+1. Assuming the two T's , T and t are the same variable, lets proceed. t+(3-2t)=4t+1 3-t=4t+1 2-t=4t 2=5t last step is yours

Subtract 21 from both sides. If that's + 4t, the answer is (t - 3)(t + 7) and t = 3, -7 If that's - 4t, the answer is (t + 3)(t - 7) and t = -3, 7

4t-10

t in this problem equals -3. 4t- 8+ 25= 5 -25 -25 4t- 8= -20 +8 +8 4t= -12 /4 /4 t= -3

3*4t = 12t

9t = 4t + 120 9t-4t = 4t - 4t + 120 5t = 120 5t/5 = 120/5 t = 24 24 is your answer

4t-523 = -519

4t-1 = t+2 3t -1 = 2 3t = 3 t = 1

t + 10 - 4t = -11 Subtract 10 from each side: t - 4t = -21 ie -3t = -21 t = -21/-3 t = 7.